Evaluation of the MBKM program integrated with the CIPP model - Dinasti Sabda Dewaji; Zainal Arifin (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study examines the effectiveness of the Integrated Merdeka Belajar Kampus Merdeka (MBKM) Program at the Department of Automotive Engineering Education, Yogyakarta State University, using the CIPP (Context, Input, Process, Product) evaluation framework. Employing a qualitative design, data were collected through semi-structured interviews with Industrial Practice (PI), Teaching Practice (PK), and Community Service (KKN) coordinators, lecturers, and industry partners, complemented by document analysis. The context evaluation indicates strong alignment between institutional objectives and national MBKM policy. However, input findings reveal gaps in student readiness, particularly in technical skills, professional attitudes, and industrial work culture. Process evaluation identifies coordination inefficiencies among PI, PK, and KKN, including overlapping implementation mechanisms and inconsistent supervision. Product evaluation shows that while most learning outcomes were achieved, limited industry understanding of MBKM activity distinctions affected mentoring effectiveness. Overall, the program demonstrates acceptable effectiveness but requires clearer operational regulations, strengthened industry communication, and enhanced student preparation to ensure more consistent and sustainable outcomes.